2019
DOI: 10.1111/1759-3441.12246
|View full text |Cite
|
Sign up to set email alerts
|

Enablers and Barriers of Tourism as a Driver of Economic and Social‐cultural Growth in Remote Queensland

Abstract: Regional and remote tourism in Australia is characterised by micro-, smalland medium-sized businesses, spatially dispersed and fragmented. Characteristics which present unique challenges for these communities attempting to develop tourism as a way of diversifying their economy. This study explored the views and experiences from residents and businesses in six remote local government areas in South Western Queensland to identify the barriers and enablers for remote communities to using tourism as a driver of ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…This study analyzed the official statistics on local accommodation establishments, Spatially fragmented and dispersed micro-or medium-sized businesses have been integrated into the economy by digital tools supported by government regulations, thereby becoming enablers of local development (Summers et al, 2019). The present case study's analyses confirmed favorable growth tendencies over the last ten years in administrative, support, health, sports, and entertainment services, which has reversed low density areas' tendency toward underdevelopment.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This study analyzed the official statistics on local accommodation establishments, Spatially fragmented and dispersed micro-or medium-sized businesses have been integrated into the economy by digital tools supported by government regulations, thereby becoming enablers of local development (Summers et al, 2019). The present case study's analyses confirmed favorable growth tendencies over the last ten years in administrative, support, health, sports, and entertainment services, which has reversed low density areas' tendency toward underdevelopment.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the current analyses' results contribute to the ongoing discussion regarding the impact of local accommodation offers on local development. This topic has been an underresearched theme, particularly with reference to remote and low density territories (Summers et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first paper by Summers, Cavaye and Woolcock () studies the enablers and barriers to tourism as a driver of economic development in regional Queensland. The purpose of the research was to explore ways regional communities in South Western Queensland could expand tourism and drive economic and social gains.…”
mentioning
confidence: 99%
“…The direction of causality of tourism driving progress just described is controversial – some hold that well‐designed economic, governance and investment policies creates a positive environment that encourages tourism to flourish. Summers et al () find that “Enablers to tourism led growth included: local government support for tourism development; a sound understanding of the mechanics and structure of the tourism industry; and the capacity to engage in marketing that captured and narrated the visitor experience in digital channels.”…”
mentioning
confidence: 99%